Helicobacter pylori infection and administration of non-steroidal anti-inflammatory drugs down-regulate the expression of gastrokine-1 in gastric mucosa - Wei MAO; Jie CHEN; Tie-Li PENG; Xiao-Fei YIN; Lian-Zhou CHEN; Min-Hu CHEN (Turkish Journal of Gastroenterology, 2019)
-